Uso da voltametria de onda quadrada e eletrodo de diamante dopado com boro no estudo de processos redox de compostos aromáticos - Alves, Eliezer de Oliveira (Universidade Federal de São Carlos, 2020)
This work presents usual concepts and examples reported in the literature on studies of redox processes involving boron-doped diamond electrodes in applications of the technique square-wave voltammetry in the development of electroanalytical methods. When analyzing the conclusions presented in the chosen works, the need to address such studies more explicitly was verified. For such, a series of tests carried out during the development of new methods for the determination of aromatic compounds were listed. These tests were chosen to create a link between the obtained experimental data and the current theoretical models addressed. The individual presentation of each test for the investigation of redox processes was chosen to facilitate the understanding of the theoretical aspects covered in this work and of the respective experimental applications. In addition to the examples, some experimental data obtained in the development of a new electroanalytical method for the detection of melamine are also presented. These data were obtained during the elaboration of this monograph. It is expected that this material can guide students and researchers with simplicity in the evaluation of different aspects of redox processes, present in the determination of aromatic compounds using square-wave voltammetry and boron-doped diamond electrodes.
The use of square-wave voltammetry and boron-doped diamond electrode in the study of redox processes of aromatic compounds
Keywords: Voltametria de onda quadrada; Eletrodos de diamante dopado com boro; Processos redox; Compostos aromáticos; Compostos heterocíclicos aromáticos; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA